Entre insultos e falsas harmonias : a construção dos efeitos de agressividade no discurso político eleitoral na campanha de 2014 - Chiari, Geovana (2017)
During the pre-election period of the presidential election in 2014, the news and commentaries about the political campaigns of the presidential candidates portrayed aggressive speeches in debates, on social media, in television campaigns, and even on official websites. This occurred both in the first round of the election and in the second, however, in a fierce dispute for winning the presidency, the second round between the President Dilma Rousseff (PT) and the former Senator Aécio Neves (PSDB) was marked by confrontation, characterized as aggressive and heated. It is important to emphasize that these news and comments about the aggressiveness of the campaign are also discursive constructions, present an impression that attest to an increase in aggressiveness, reason why we cannot consider them as a presupposition and a starting point for analysis. However, the constant reproduction of discourses that characterize the campaign of 2014 as aggressive, already constitutes a pertinent indicator for analysis of what was understood as insult, aggression. Other important issues that drive us to look at this campaign are the change in the organization of television debates - direct interaction between the candidates, positioned face to face -, the intensification of the use of social networks, as well as the candidates' official sites, among other aspects that would favour a possible increase of the aggressiveness or the production of a greater visibility of what is considered aggressive. Given the peculiarities of the organization and functioning of the mediums (debates, sites, social networks and blogs) in this campaign, and the emergence of discourses that characterize it as aggressive, we attempt to analyze the discourse said aggressive, trying to understand its formulation and materialization in the political discourse through the resources of irony, theme selection, derisive speech, swearing, gestures, tone of speech, allusion, among others. What would be the aggressive, bitter, disrespectful discourse? How does it materialize in political discourse? Guided by these research questions and based on the theory of French Discourse analysis, we propose the analysis of televised political debates, images that circulated in social networks (Facebook, Blogs), as well as on the official websites of the campaigns, during the pre-election period, with the goal of understanding, currently, the production and circulation of the discourse so-called aggressive in Brazil.